Premotor Diagnosis of Parkinson’s Disease - Reichmann, Heinz (Neurosci Bull, 2017)
Typical Parkinsonian symptoms consist of bradykinesia plus rigidity and/or resting tremor. Some time later postural instability occurs. Pre-motor symptoms such as hyposmia, constipation, REM sleep behavior disorder and depression may antecede these motor symptoms for years. It would be ideal, if we had a biomarker which would allow to predict who with one or two of these pre-motor symptoms will develop the movement disorder Parkinson’s disease (PD). Thus, it is interesting to learn that biopsies of the submandibular gland or colon biopsies may be a means to predict PD, if there is a high amout of abnormally folded alpha-synuclein and phosphorylated alpha-synuclein. This would be of relevance if we would have available means to stop the propagation of abnormal alpha-synuclein which is otherwise one of the reasons of this spreading disease PD.